O “Atualismo” de Pereira & Araújo: Entre metafísica do tempo histórico e regime de historicidade - Cardoso, Helio Rebello [UNESP] (Universidade Federal de Goias, 2023)
“Updatism” or “updatist historicity” is a concept that has become part of the recent theory of history. This concept unfolds into two stages. First, it presents a historical-transcendental scope since it involves conditions of possibility according to which time can be historically experienced. Secondly, it is a heuristic-historiographical tool, insofar as it allows gathering and analyzing the updatist historical experiences under a steady focus. Therefore, it is possible to observe that the Heideggerian transcendental safeguard to which Pereira and Araujo appeal is a way of preserving the heuristic function of the concept, preventing it from being confused with the reality under its extension. Consequently, it is discussed Pereira and Araujo’s critique regarding Hartog’s “presentism” as a heuristic-historiographical concept, however, it is noted that this critique cannot be extended to Gumbrecht’s “broad present”.
Entre metafísica do tempo histórico e regime de historicidade